(untitled) (Bangladesh Journal of Medical Science, 2023)
Clustered Regularly InterSpaced Palindromic Repeats is known as CRISPR. It is a protein that can be programmed to change, eliminate, or activate the genome. This cutting-edge technology offers a broad range of possible implementation and is poised to revolutionise oral healthcare in the years to come. The most widely utilised genome editing techniques include homing endonucleases, Transcription Activator-Like Effector Nucleases, Zinc-Finger Nucleases, and CRISPR- CRISPR-associated protein 9 (Cas9). These adaptable genome-editing tools can alter the genomes in ways that are sequence-specific. Because it is highly effective and accurate, the genome editing method CRISPR-Cas9 has drawn attention as a potent weapon in the fight against cancer. This method and its uses, particularly in dental field, are covered in this review. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.42-46